Impairment of skeletal muscle oxygen extraction and cardiac output are matched in precapillary pulmonary hypertension. Issue 3 (31st August 2021) - Stubbs, Harrison; Church, Colin; Johnson, Martin; Thomson, Stephen
Pulmonary arterial hypertension (PAH) is characterised by pathological pulmonary vascular remodelling and increased resistance leading to right heart failure and death [1]. It is thought that exercise intolerance in PAH arises from an impairment in oxygen transport and delivery, driven by a reduced stroke volume [2]. In precapillary pulmonary hypertension, exercising muscles extract oxygen to a similar level seen in healthy individuals. Exercise limitation is a result of impaired oxygen delivery, which is matched to any impairment in skeletal muscle oxygen extraction. https://bit.ly/3hQUY8m